2014
DOI: 10.3402/ejpt.v5.23870
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic experiences, alexithymia, and posttraumatic symptomatology: a cross-sectional population-based study in Germany

Abstract: ObjectivePrevious studies have established an association between number of traumatic experiences and alexithymia. The present study examines this relationship in a large-scale representative sample of the German general population (N=2,507) and explores the potential mediating effects of posttraumatic symptomatology, particularly avoidance/numbing.MethodsAlexithymia was assessed with the German version of the Toronto Alexithymia Scale (TAS-20). Posttraumatic symptomatology was operationalized by the symptom s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 48 publications
4
31
0
Order By: Relevance
“…Further evaluation of those who do not or cannot cry by their partners and colleagues is needed with the use of behavioral and implicit measures in addition to self-reports in order to clarify the potential bidirectional associations between an incapacity to cry and different clinical conditions (e.g., PTSD, psychopathy, and depression) and alexithymia (i.e., the inability to understand and express emotion). Alexithymia is also associated with a history of emotional trauma 30 and with somatoform disorders such as non-epileptic seizures (pseudoseizures), which present considerable therapeutic challenges. 30 Finally, future work should assess how the present findings fit into concepts like alexithymia, emotional suppression, and emotional numbness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further evaluation of those who do not or cannot cry by their partners and colleagues is needed with the use of behavioral and implicit measures in addition to self-reports in order to clarify the potential bidirectional associations between an incapacity to cry and different clinical conditions (e.g., PTSD, psychopathy, and depression) and alexithymia (i.e., the inability to understand and express emotion). Alexithymia is also associated with a history of emotional trauma 30 and with somatoform disorders such as non-epileptic seizures (pseudoseizures), which present considerable therapeutic challenges. 30 Finally, future work should assess how the present findings fit into concepts like alexithymia, emotional suppression, and emotional numbness.…”
Section: Discussionmentioning
confidence: 99%
“…Alexithymia is also associated with a history of emotional trauma 30 and with somatoform disorders such as non-epileptic seizures (pseudoseizures), which present considerable therapeutic challenges. 30 Finally, future work should assess how the present findings fit into concepts like alexithymia, emotional suppression, and emotional numbness. 31…”
Section: Discussionmentioning
confidence: 99%
“…In their study of male patients with adjustment disorder, Na et al (16) determined that, compared to the healthy This study showed a positive correlation between the alexithymia levels and traumas experienced in childhood. In their study of German society, Eichhorn et al (17) determined that the more that traumatic experiences of patients increase the more their alexithymia levels increase. The findings of this study demonstrate that therapies for the treatment of traumas can be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, it is also considered one of the factors that plays a role in coping with stress are alexithymic features (16,17). Alexithymia, which is described as the difficulty recognizing and describing emotions and the difficulty distinguishing physical and emotional sensations, reduces the resistance of the individual to stress and limits the capacity of the person to adapt (17,18). Studies have reported alexithymia to be common in psychiatric disorders (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…18,19 In recent studies, alexithymic features have been identified not only in psychiatric disorders but also in the healthy population. 20,21 Son et al 22 note that the prevalence of alexithymia is 10-18% in the general population and 7.6-39.8% in psychiatry outpatients. Studies about alexithymia and its prevalence among university students are relatively limited.…”
Section: Introductionmentioning
confidence: 99%